Open Fault Tolerant Method Using DPWM for Reducing Switching Loss in Three-Level Hybrid ANPC Inverter - Jo, Ha Rang; Ko, Youngjong; Lee, Kyo Beum (5th IEEE Conference on Energy Conversion, CENCON 2021, 2021)
This paper proposes an open fault tolerant control for reducing switching loss in a three-level Si/SiC hybrid active neutral-point clamped (HANPC) inverter. The Si/SiC hybrid ANPC inverter consists silicon (Si) switches and silicon-carbide (SiC) switches. The HANPC inverter is more economical compared to the full SiC ANPC inverter and the full SiC ANPC inverter provides the high efficiency and power density almost the same as the full-SiC ANPC inverter. The Si switches operate with the low switching frequency according to the fundamental frequency, and the SiC switches have the high switching frequency depend on the carrier-based switching methods. The HANPC inverter has two neutral-states which make the pole voltage zero. Even if one of the Si switches for generating the neutral-states has an open fault, therefore, the inverter can output the normal three-phase current with the tolerant control. When the open fault tolerant control is applied, however, the Si switches operate with the high switching frequency same as the SiC switches. As a result, the Si switches have the high switching loss and overheat. To solve this problem, the fault tolerant control using discontinuous pulse width modulation (DPWM) is proposed in this paper. The proposed method is verified through simulation results.
Keywords: Active neutral point clamped; Discontinuous pulse width modulation; Faults tolerant controls; Loss reduction; Neutral-point clamped inverters; Open switch fault; Pulsewidth modulations (PWM); Switch faults; Switch loss; Switch loss reduction; Three-level; Three-level hybrid active neutral-point clamped inverte; DPWM; Fault tolerant control; Open switch fault; Switch loss reduction; Three-level HANPC inverter